Bisexual identity denial and health: Exploring the role of societal meta-perceptions and belonging threats among bisexual adults. Issue 4 (19th May 2021) - Maimon, Melanie R.; Sanchez, Diana T.; Albuja, Analia F.; Howansky, Kristina
ABSTRACT: Bisexual individuals frequently experience identity denial from others due to perceptions that bisexuality is an illegitimate identity. Bisexual individuals have worse psychological health than gay, lesbian, and heterosexual people, but the reasons for these disparities are not well understood. Across a two-sample correlational study (Total N = 445) utilizing path analyses, we tested belonging uncertainty, bisexual meta-stereotypes, and meta-legitimacy perceptions as mediators of the relationship between identity denial and depressive symptoms. More frequent identity denial was related to greater belonging uncertainty, greater bisexual meta-stereotypes, lower meta-legitimacy, and greater reported depressive symptoms, with belonging uncertainty mediating the relationship between identity denial and depressive symptoms. These findings suggest that identity denial is related to the social and psychological health of bisexual individuals.